Identification of Aquaporin 3 Inhibitors from Santalum album Phytochemicals for Melanoma treatment: A Computational Study: Targeting Aquaporin 3: Santalum Album in Melanoma Therapy - Alam, Mudassir; Abbas, Kashif; Raza, Mohd Tanjeem; Abedi, S Mohd Hasan; Haq, Hafsa; Mustafa, Mohd (Iranian Journal of Pharmaceutical Sciences, 2024)
This study employed a multifaceted computational approach to identify potential inhibitors of aquaporin 3 (AQP3) derived from phytochemicals found in the Santalum album as potential drug candidates for melanoma treatment. Initially, the AQP3 structure was modeled using SWISSMODEL, which yielded a satisfactory GMQE score of 0.70 and a MolProbity score of 1.61. The QMEAN Z-score (-3.29) indicated acceptable quality, and Ramachandran analysis revealed that 95.12% of the residues were within the favored region. Virtual screening of phytochemicals utilized AutoDock Vina to identify compounds with strong binding affinity for AQP3. Phytochemicals exhibiting docking scores of -7 or less were selected for further analysis. The physicochemical properties and drug-likeness were evaluated using SWISS ADME, revealing compounds with favorable solubility, permeability, and gastrointestinal absorption. Biological activity prediction through the PASS web server indicated significant probabilities of dermatologic and antineoplastic activities for selected compounds. ADME/T properties were analyzed using the ADMET Lab 2.0 server, demonstrating favorable pharmacokinetic characteristics and safety profiles for compounds such as alpha-bergamotenol, himachalol, lupeol, levomenol, and sclareol. Except for himachalol, the other phytochemicals showed good safety profiles. Apart from himachalol, the remaining phytochemicals demonstrated favorable safety profiles. Molecular dynamics (MD) simulations provided insights into the stability and flexibility of receptor-ligand complexes over time, with compounds such as sclareol and levomenol exhibiting stable interactions. This comprehensive computational investigation highlights the potential of phytochemicals from S. album, particularly levomenol and sclareol, as inhibitors of AQP3. Further experimental validation is necessary to explore their clinical application in treating dermatologic conditions and cancer.